SIMADU: Integrated Application to Support Student Activities in University - Muhammad Faishal Afiq; Abang Charil Ralfi Permana; Abdullah Hudan; Fauzan Firdaus; Vina Dwiyanti (Universitas Pendidikan Indonesia, 2023)
Electronic-based academic information systems such as websites are needed to support student activities. In its development, the academic and lecture information is stored in a website hosting, in order to make it easier to access the information from anywhere as long as it is connected to the internet. However, according to the Higher Education Database (PDDikti) that the website is constrained when accessed via a mobile device (mobile), due to the large amount of data to be accessed where the specifications of mobile devices are sometimes limited. So it is necessary to develop an application to access academic information based on mobile devices or smartphones. This study uses the ADDIE model method. Based on the results of a survey of Universitas Pendidikan Indonesia students, 43.6% of students were dissatisfied with the website-based academic information system. Students feel ineffective in using too many websites so that it is confusing and troublesome for students to access the information they need. So to simplify the above, it is necessary to conduct research to utilize information and communication technology in supporting the smooth process of distributing academic and lecture information in the form of a tool in the form of an application program called SIMADU.